Dialectical Logic K-Model: Some Applications by Fuzzy-Probability Theory, Cause -Effect Analysis, Chaos Dynamics and Optimization Theory - Jiang, Yaozhi (Transactions on Engineering and Computing Sciences, 2019)
The paper is a further successor about some problems in dialectical logic K-model which maybe a new useful tool in Artificial Intelligence. The first problem is for the case that true value function is produced by the method of fuzzy-probability theory, this discussion is based on a famous work by Zadeh L. A. (Zadeh L. A., 1965); the second problem is a result about cause-effect analysis, a proof is given for the theorem “a regular cause-effect graph must be a tree-graph”, therefor any mathematical formula can be expressed into a cause-effect tree-graph; the third problem is research for chaos dynamics of contradiction function onto magnitude-frequency characteristics; the last problem is discussion about optimization in dialectical logic K-model and a mathematical model about optimization is built up.